The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1177/1010539513496136
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Poor Response After Primary Immunization of Hepatitis B Vaccines for Infants and Antibody Seroprotection of Booster in a Metropolis of China

Abstract: To evaluate proportion and predictors of poor response in infants and appraise booster seroprotection, we surveyed 2047 infants in Shanghai and detected antibody to hepatitis B (HB) surface antigen (anti-HBs). Poor responders were randomized into 2 groups, given booster with 5 µg and 10 µg hepatitis B vaccine (HepB), respectively. Proportion of infants with titer <10 mIU/mL and 10 to 99 mIU/mL was 1.86% and 15.14%, respectively. Multivariate logistic regression suggested infants of male, aged 13 to 18 months, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…The rate of weak positive response is comparable to the study by Li et al ., despite a higher dose of HBV vaccine (10 vs. 5 μg) given in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The rate of weak positive response is comparable to the study by Li et al ., despite a higher dose of HBV vaccine (10 vs. 5 μg) given in our study.…”
Section: Discussionsupporting
confidence: 89%
“…The Centers for Disease Control guidelines define the post‐vaccination anti‐HBs response as immune if the anti‐HBs titres are higher than 10 IU/L. However, there are studies by European and Chinese groups showing that infants born to chronic hepatitis B carrier mothers are also at risk of horizontal transmission from their mothers and family members. Hence, these infants should ideally achieve and maintain anti‐HBs titre greater than 100 IU/L.…”
Section: Discussionmentioning
confidence: 99%
“…Sex is also a predictor of response and male infants are more likely to have an inferior response than female infants. 24,36 Various theories resulting from several studies found a decrease in the number of T lymphocytes in males compared to females, and men have lower serum IgM and IgG levels. The different immune response between male and female is also influenced by sex steroid hormones such as estrogen, progesterone, and testosterone, which are different in each sex.…”
Section: Discussionmentioning
confidence: 99%
“…4,[20][21][22][23][24] Farklı oranların gözlenmesinde ülkelerin HBV açısından endemisite statülerindeki, ilk aşılama yaşındaki, aşılama programları çizelgesindeki, aşı tipindeki (plazma bazlı ve rekombinant), uygulanan doz miktarındaki, doz sayısındaki ve uygulama yolundaki farklılıkların etkili olduğu düşünülmektedir. 1,4,25,26 İmmünsupresyon ve obezite gibi ek faktörlerin de hem anti-HBs reaktivite oranlarını hem de anti-HBs titre değerlerini etkileyebileceği bildirilmiştir. 1,4,20,27 Çalışmamızda, anti-HBs için reaktif ve nonreaktif olan gruplar arasında cinsiyet dağılımı açısından istatistiksel olarak anlamlı farklılık saptanmıştır.…”
Section: Discussionunclassified